2015
DOI: 10.1111/aos.12642
|View full text |Cite
|
Sign up to set email alerts
|

Cycloplegic refraction is the gold standard for epidemiological studies

Abstract: ABSTRACT. Many studies on children have shown that lack of cycloplegia is associated with slight overestimation of myopia and marked errors in estimates of the prevalence of emmetropia and hyperopia. Non-cycloplegic refraction is particularly problematic for studies of associations with risk factors. The consensus around the importance of cycloplegia in children left undefined at what age, if any, cycloplegia became unnecessary. It was often implicitly assumed that cycloplegia is not necessary beyond childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
146
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(159 citation statements)
references
References 53 publications
11
146
1
1
Order By: Relevance
“…The lack of cycloplegia in the current study may have caused some of our subjects below the age of 50 to accommodate during measurement, which would increase lens power in the younger age categories, thus steepening the lens power decrease on the left-hand side of Figure 2. The influence of this effect can be estimated by referring to a recent article by Morgan et al, 26 who found that in subjects aged 20 to 50 years the mean difference between cycloplegic and noncycloplegic refraction can be up to 0.20 to 0.25 D for myopes and emmetropes, and up to 0.50 to 0.65 D for hypermetropes. This corresponds with lens power increases of 0.37 and 0.95 D for myopes/emmetropes and hypermetropes, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of cycloplegia in the current study may have caused some of our subjects below the age of 50 to accommodate during measurement, which would increase lens power in the younger age categories, thus steepening the lens power decrease on the left-hand side of Figure 2. The influence of this effect can be estimated by referring to a recent article by Morgan et al, 26 who found that in subjects aged 20 to 50 years the mean difference between cycloplegic and noncycloplegic refraction can be up to 0.20 to 0.25 D for myopes and emmetropes, and up to 0.50 to 0.65 D for hypermetropes. This corresponds with lens power increases of 0.37 and 0.95 D for myopes/emmetropes and hypermetropes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may have introduced a small refractive shift, especially in the subjects below the age of 50. 26 …”
Section: Subjectsmentioning
confidence: 99%
“…All three readings had to be at most 0.50D apart in both the spherical and cylinder components. One per cent cyclopentolate was used to achieve full cycloplegia,6 due to the difficulty of achieving complete cycloplegia in younger subjects with darker irises 4. For each student, one drop of 1% cyclopentolate (Alcon) was administered first, followed by one drop of Mydrin P (Tropicamide 0.5%, phenylephrine HCl 0.5%; Santen Pharmaceutical, Shiga, Japan) and then a second drop of 1% cyclopentolate at 5 min interval between each of the drops 21.…”
Section: Methodsmentioning
confidence: 99%
“…It is thus an important indicator in paediatric ophthalmology,1 cataract2 and refractive surgery,3 and many epidemiological studies of refractive status have been performed 4. As the capacity for accommodation exists, it is challenging to accurately measure refractive status without cycloplegia 4. However, in epidemiological studies, cycloplegia is particularly more challenging than in clinical situations, because of the time involved and the side-effects associated with cycloplegia, such as blurred vision and photophobia.…”
Section: Introductionmentioning
confidence: 99%
“…However, the condition of cycloplegia is required for studying refraction in patients until the age of 20 years (Sanfilippo et al 2014). Moreover, the condition of cycloplegia is also required for epidemiological studies of refraction in patients aged over 50 years (Morgan et al 2015). Therefore, we need to examine how pupil dilation due to covering one eye affects the refraction in the condition of cycloplegic refraction.…”
mentioning
confidence: 99%